Telemental Health Assessment of Adolescents During the COVID-19 Pandemic: A Follow-up Study - Birsen Şentürk Pilan; İpek İnal Kaleli; Didem Çek; Tuğçe Özcan; Faig Azizov; Samira Huseynova; Gizem Cengiz; Sezen Köse; Burcu Özbaran; Zeki Yüncü; Serpil Erermiş; Tezan Bildik (Galenos Yayinevi, 2023)
Aim:This study aimed to understand how the pandemic has affected the mental health of adolescents with a previous psychiatric diagnosis.Materials and Methods:Fifty-nine patients aged 12-18 years who had been previously followed up in the adolescent mental health unit were included in this study. The participants were interviewed via telephone between June-July, 2020 and December, 2020-January 2021. Their socio-demographic data, psychiatric diagnoses and the previous Clinical Global Impression (CGI) scores were obtained from the patient files. The clinical global follow-up scale was scored by the interviewing physician.Results:Past CGI scores before the pandemic were significantly greater for those participants with more than one psychiatric condition (p=0.024). For those participants with more than one psychiatric condition, the difference between the CGI scores prior to the pandemic and during the early stages of the pandemic were significant (p=0.004). The total satisfaction scores for telepsychiatry services assessed via the telemedicine evaluation form were statistically higher for those participants with a single psychiatric disorder (p=0.023). The past and early pandemic CGI scores were found to be inversely correlated with the telemedicine evaluation form with r=-0.338, p=0.019, r=-0.353 p=0.014, respectively.Conclusion:The present study offers a perspective for adolescent mental health during the pandemic, underlining the importance and caveats of healthcare delivery to the youth with mental health problems during lockdown.